2017
DOI: 10.1073/pnas.1701315114
|View full text |Cite
|
Sign up to set email alerts
|

Impact of glacial/interglacial sea level change on the ocean nitrogen cycle

Abstract: The continental shelves are the most biologically dynamic regions of the ocean, and they are extensive worldwide, especially in the western North Pacific. Their area has varied dramatically over the glacial/interglacial cycles of the last million years, but the effects of this variation on ocean biological and chemical processes remain poorly understood. Conversion of nitrate to N by denitrification in sediments accounts for half or more of the removal of biologically available nitrogen ("fixed N") from the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 76 publications
7
72
0
Order By: Relevance
“…After removing the glacial‐interglacial cycle trend, the detrended δ 15 N Src (δ 15 N Src‐residue ) displays a clear precession cycle paralleled to the δ 15 N bulk record, especially during MIS5 and MIS7 (Figure d). The precession cycle is also extensively found in FB‐δ 15 N record in the eastern SCS (Ren et al, ) and δ 15 N org records in the southern SCS (Dong et al, ; results of spectral analyses are shown in the supporting information). Previous study by Ren et al () suggest that the N fixation changes of the SCS are mainly controlled by sea level‐driven glacial/interglacial oscillations in excess phosphorous fluxes at and near the ocean margins.…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…After removing the glacial‐interglacial cycle trend, the detrended δ 15 N Src (δ 15 N Src‐residue ) displays a clear precession cycle paralleled to the δ 15 N bulk record, especially during MIS5 and MIS7 (Figure d). The precession cycle is also extensively found in FB‐δ 15 N record in the eastern SCS (Ren et al, ) and δ 15 N org records in the southern SCS (Dong et al, ; results of spectral analyses are shown in the supporting information). Previous study by Ren et al () suggest that the N fixation changes of the SCS are mainly controlled by sea level‐driven glacial/interglacial oscillations in excess phosphorous fluxes at and near the ocean margins.…”
Section: Resultssupporting
confidence: 61%
“…The δ 15 N records from these three sites all present glacial‐interglacial variations of ~3‰, with distinct lower values in interglacial periods. The FB‐δ 15 N is supposed to faithfully represent the subsurface nitrate δ 15 N (Ren et al, ), as the late Holocene FB‐δ 15 N in SCS cores average 5.60‰ (Ren et al, ), close to the modern subsurface nitrate δ 15 N (Figure a). The MD05‐2901 δ 15 N Src varies in the same pattern and amplitude as those FB‐δ 15 N over the last 250 ka but shows a systematic offset of about +1‰ (Figure c).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations